Prestress Losses in Concrete Rafters with Openings - Alkhafaji, F. J.; Izzet, A. F. (Engineering, Technology & Applied Science Research, 2020)
In this paper, experimental work was conducted to evaluate the losses in prestressing force of 13 (12 perforated and 1 solid) simply supported prestressed concrete rafters. All beams had the same dimensions and reinforcements. The tested beams were divided into four main groups and three additional subgroups were driven. These groups were classified according to size, number, and configuration of the openings, and the orientation of the posts (vertical or inclined). Regarding the prestress losses that have been affected by the cross-section properties, the provision of the codes is applicable only to prismatic solid beams, so non-prismatic or moreover perforated beams also need to be studied. This paper aims to propose a method based on the same code provisions but taking into consideration the cross-section variation along the beam length. The proposed method divides the overall length of the rafter into a number of assumed prismatic segments with heights measured at centers. Then, the overall prestress loss is found as the sum of these segments weighed by the ratios of the length of each beam segment to the overall length. The experimental results of the proposed method ranged from 84.749% to 95.607% denoting its validity.